Studying sensitive and contradictory family situations: Considerations from three family studies (Journal of Comparative Social Work, 2011)
The purpose of this article is to discuss questions about studying sensitive and contradictory family situations, particularly in the process of gathering qualitative data via interviews. In the article, the authors ask what types of considerations are possible when studying such issues. Three ongoing family studies conducted in the social sciences by the authors are used as the basis for discussing the sensitive and contradictory nature of such family issues. The authors’ studies are about the foster children’s family relations, the sons of problem-drinking fathers and the families participating in a preventive family support system. Family matters are often perceived as being something private that is not to be talked about or shared with outsiders, e.g. talking about negative feelings towards family members may be complicated.